SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN KONDISI JALAN DI TALANG KELAPA KABUPATEN BANYUASIN (Universitas Muhammadiyah Palembang, 2022)
Banyuasin Regency is one of the regencies located in South Sumatra Province has a fairly extensive roadnetwork and is a cross-city link. The problem faced is that many roads are damaged, and inadequatereporting systems result in slow repairs. Therefore, a better road condition reporting system is needed, sothat the priority of handling road conditions is right on target. integrated mapping of the city's roadnetwork by utilizing the Geographic Information System as a solution to solving these problems. Thisresearch was conducted by collecting road network data and road condition surveys using the SurfaceDistress Index (SDI) method on road sections in Talang Kelapa along 142.7 km, after completing roadcondition data then created a database of all road condition information with the GIS application. Basedon the analysis obtained SDI value parameters from a total of 142.7 km of road sections in TalangKelapa, Banyuasin Regency, there are 46.8 km (32.8%) of road conditions in the